Surface treatment method based on laser shock
By using a laser shock-based surface treatment method, the pattern is formed by using a laser beam to solve the problem of insufficient wear resistance on the surface of laser texture, and the effect of improving surface wear resistance and durability is achieved.
Patent Information
- Application Number
- CN202510019939.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
AI Technical Summary
Existing laser-textured surfaces are prone to deterioration during long sliding periods, mainly due to the low wear resistance of the surface texture, which limits its service life.
Using a surface treatment method based on laser shock, a metal mold with a hollowed-out area is placed between the metal sample to be processed and the constraint layer is irradiated with a laser beam in a direction perpendicular to the constraint layer to form a pattern to improve surface wear resistance and durability.
This method can produce a deformation-proof surface with a patterned array, improve the contact angle, friction coefficient and hardness of the metal sample to be processed, thereby enhancing its wear resistance and durability.
Smart Images

Figure CN119824211A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of laser processing, and in particular to a surface treatment method based on laser shock. Background Art
[0002] Laser shock peening (LSP) is an advanced surface treatment method. Its core is to use the interaction between laser and material to induce ultra-high strain rate plastic deformation (10 5 –10 6 / s), which will introduce a work-hardened surface layer and compressive residual stresses.
[0003] In the pursuit of higher performance surface treatment, surface patterning processes have made great progress, including grinding, etching, embossing and laser surface texturing (LST). These processes effectively control the coefficient of friction (COF) and extend the lubrication life by creating specific patterned textures on the surface of the material. Among them, the LST process has the advantages of scalability, non-contact processing, no need for hard tools, high flexibility and excellent resolution. LST uses the interaction between ultrashort laser pulses and surface materials to achieve precise ablation and generate surface microfeatures such as micropits. These microfeatures can act as microreservoirs of lubricants under lubrication conditions, and act as microtraps for wear debris under lubrication or dry sliding conditions, effectively regulating friction behavior.
[0004] However, although laser-textured surfaces excel in mechanical applications due to their controllable coefficient of friction, these surface textures are susceptible to degradation during prolonged sliding. This degradation is mainly attributed to the low wear resistance of the surface textures, a problem that limits the service life of laser-textured surfaces.
[0005] In view of the above problems, there is an urgent need to develop a new surface patterning process to improve the durability of surface textures. Summary of the invention
[0006] The purpose of this application is to provide a surface treatment method based on laser shock to solve the above problems.
[0007] To achieve the above objectives, this application adopts the following technical solutions:
[0008] A surface treatment method based on laser shock, comprising: placing a metal mold with a hollow area between a metal sample to be processed and a constrained layer, irradiating a laser beam to the metal sample to be processed in a direction perpendicular to the constrained layer, and forming a pattern on the metal sample to be processed under the action of the laser shock wave;
[0009] The energy density of the laser shock wave is less than 3.25 GW / cm 2, the thickness of the metal mold is greater than 10 μm, and the pulse width of the laser shock wave is less than 30 ns.
[0010] According to an embodiment of the present application, the material of the metal sample to be processed includes any one of pure titanium, pure iron, magnesium alloy, and steel.
[0011] According to an embodiment of the present application, the material of the metal mold includes brass or nickel-based alloy.
[0012] According to an embodiment of the present application, a sacrificial layer is further provided between the metal sample to be processed and the constraining layer, the sacrificial layer comprises a black organic tape, and the thickness of the sacrificial layer is 50-200 μm.
[0013] According to an embodiment of the present application, the sacrificial layer is located between the constrained layer and the metal mold.
[0014] According to an embodiment of the present application, the sacrificial layer is located between the metal mold and the metal sample to be processed.
[0015] According to an embodiment of the present application, the thickness of the metal mold is 20-100 μm.
[0016] According to an embodiment of the present application, the pulse width of the laser shock wave is greater than or equal to 10 ns and less than 30 ns.
[0017] According to an embodiment of the present application, the energy density of the laser shock wave is 0.5-3.2 GW / cm 2 .
[0018] According to an embodiment of the present application, the constraint layer is tempered glass or a water flow layer, and the thickness of the constraint layer is 2-8 mm.
[0019] Compared with the prior art, the beneficial effects of this application include:
[0020] The present application utilizes laser-induced shock wave loads to simultaneously introduce surface strengthening effects and patterning effects, and can produce an anti-deformation surface with a patterned array, which can enhance the wear resistance and durability of the metal sample to be processed. Specifically, the contact angle and COF of the metal sample to be processed can be improved by using the method of the present application, and the hardness of the metal sample to be processed can be improved, and the wear resistance and durability of the metal sample to be processed can be improved, which effectively improves the problem of poor durability of the existing surface patterning process. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0022] Figure 1 A diagram showing the relative position relationship between a metal sample to be processed and a metal mold in one embodiment of the present application;
[0023] Figure 2 is a diagram showing the relative positions of the metal sample to be processed and the metal mold in another embodiment of the present application;
[0024] Figure 3 is a SEM image of the surface of a pure titanium sample treated by the method of Example 1;
[0025] Figure 4 is a comparison diagram of the contact angles of the pure titanium sample before and after being treated using the method of Example 1;
[0026] Figure 5 is a SEM image of the surface of a pure titanium sample treated by the method of Example 2;
[0027] Figure 6 is a comparison diagram of the contact angles of the pure titanium sample before and after being treated using the method in Example 2;
[0028] Figure 7 is a SEM image of the pure iron surface treated by the method of Example 3;
[0029] Figure 8 is a SEM image of the surface of AZ31B magnesium alloy treated by the method of Example 4;
[0030] Fig. 9 is a SEM image of the surface of 1045 steel treated by the method of Example 5;
[0031] Fig.10 This is a SEM image of the pure titanium surface treated using the method of Comparative Example 1.
[0032] Description of Reference Numerals
[0033] 100-metal mold, 200-metal sample to be processed, 300-constraint layer, 400-sacrificial layer, A-laser beam, a-plasma. DETAILED DESCRIPTION
[0034] As used herein:
[0035] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0036] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0037] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0038] In these examples, parts and percentages are by mass unless otherwise indicated.
[0039] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0040] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0041] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:
[0042] A surface treatment method based on laser shock, reference Figure 1 and Figure 2 , comprising: placing a metal mold 100 having a hollow area between a metal sample 200 to be processed and a constrained layer 300, irradiating a laser beam A to the metal sample 200 to be processed in a direction perpendicular to the constrained layer 300, and forming a pattern on the metal sample 200 to be processed under the action of the laser shock wave;
[0043] Among them, the energy density of the laser shock wave is less than 3.25GW / cm 2 , the thickness of the metal mold 100 is greater than 10 μm, and the pulse width of the laser shock wave is less than 30 ns.
[0044] According to an embodiment of the present application, the method further includes pre-treating the metal sample 200 to be processed, thereby reducing the surface roughness of the metal sample 200 to be processed and achieving a better pattern effect. Specifically, the pre-treating of the metal sample 200 to be processed includes: before the laser beam A irradiates the constrained layer 300, the surface of the metal sample 200 to be processed is mechanically polished and polished, and finally ultrasonically treated with alcohol. Mechanical polishing includes wet sandpaper polishing, and polishing includes polishing using a diamond polishing suspension and a colloidal silica suspension in sequence.
[0045] According to an embodiment of the present application, the material of the metal sample 200 to be processed includes any one of pure titanium, pure iron, magnesium alloy, and steel.
[0046] According to an embodiment of the present application, the material of the metal mold 100 includes brass or nickel-based alloy. These materials have low thermal expansion coefficient and high heat resistance, have high stability under high energy impact, and can form a precise pattern on the metal sample 200 to be processed.
[0047] Furthermore, the hollow area may include a plurality of sub-hollow areas distributed in an array, and the shapes of the sub-hollow areas may be the same or different. The shapes of the sub-hollow areas include regular shapes or irregular shapes, wherein regular shapes include but are not limited to circles, squares, and rectangles, and the size of the sub-hollow areas may be adjusted according to the use requirements, for example, the size of the sub-hollow areas may be 10-90 μm.
[0048] According to an embodiment of the present application, a sacrificial layer 400 is further provided between the metal sample 200 to be processed and the constrained layer 300. The sacrificial layer 400 includes a black organic tape and has a thickness of 50-200 μm. The sacrificial layer 400 can absorb laser energy and protect the metal mold 100 and the target sample surface from unnecessary laser damage.
[0049] For example, the thickness of the sacrificial layer 400 may be 50 μm, 100 μm, 150 μm, 200 μm, or any value between 50-200 μm.
[0050] The method of the present application includes an indirect LSSP method and a direct LSSP method. The indirect LSSP method can produce pits on the metal sample 200 to be processed, and the direct LSSP method can produce protrusions on the metal sample 200 to be processed, and surface applications with different positive and negative inclinations can be realized. The pits have good friction and wear properties, and the surface of the protrusions has good anti-stick properties.
[0051] According to an embodiment of the present application, Figure 1 A schematic diagram of the indirect LSSP method is shown. Figure 1 (a) is the position relationship diagram of the metal sample to be processed and the metal mold in the indirect LSSP method. Figure 1 (b) is a comparison of the metal sample before and after treatment using the indirect LSSP method. Figure 1 As shown, the sacrificial layer 400 is located between the constraining layer 300 and the metal mold 100. The metal mold 100 with micro features is placed on the surface of the metal sample 200 to be processed, and the sacrificial layer 400 covers the metal mold 100 and the metal sample 200 to be processed, and ensures that there is no gap between the surface of the metal sample 200 to be processed and the sacrificial layer 400. A transparent constraining layer 300 is placed above the sacrificial layer 400 to limit the fluid dynamic expansion of the laser-induced plasma a, thereby generating a laser-induced shock wave with a high peak pressure. Once the peak pressure of the laser-induced shock wave is higher than the dynamic yield strength of the target material, the shock wave causes plastic deformation below the hollowed-out area of the metal mold 100, thereby forming a surface with a series of micro pits on the metal sample 200 to be processed. In this process, the metal mold 100 acts as a mask and a patterned buffer pad, and does not directly interact with the laser energy.
[0052] According to some embodiments of the present application, when the sacrificial layer 400 is located between the constrained layer 300 and the metal mold 100, that is, when the indirect LSSP method is adopted, the thickness of the metal mold is preferably 20-50μm, for example, it can be 20μm, 30μm, 40μm, 50μm or any value between 20-50μm.
[0053] According to an embodiment of the present application, Figure 2 A schematic diagram of the direct LSSP method is shown. Figure 2 (a) is the position relationship diagram of the metal sample to be processed and the metal mold in the direct LSSP method. Figure 2 (b) is a comparison of the metal sample before and after treatment using the direct LSSP method. Figure 2As shown, the sacrificial layer 400 is located between the metal mold 100 and the metal sample 200 to be processed. The metal mold 100 with micro features is placed on the sacrificial layer 400, and the sacrificial layer 400 tightly covers the metal sample 200 to be processed. A transparent constraining layer 300 is placed above the metal mold 100 to limit the hydrodynamic expansion of the laser-induced plasma a, thereby generating a laser-induced shock wave with a high peak pressure. Since there is a gap between the constraining layer 300 and the sacrificial layer 400 in the hollowed-out area of the metal mold 100, only the non-hollowed-out part of the metal mold 100 is tightly restricted by the constraining layer 300, which will generate a shock wave with a peak pressure of several GPa, which propagates to the surface of the metal sample 200 to be processed, causing plastic deformation of the surface of the metal sample 200 to be processed. Therefore, the impact load caused by the shock wave plastically imprints the micro features of the metal mold 100 onto the surface of the metal sample 200 to be processed, forming a surface with a series of micro protrusions on the metal sample 200 to be processed.
[0054] According to some embodiments of the present application, when the sacrificial layer 400 is located between the metal mold 100 and the metal sample 200 to be processed, that is, when the direct LSSP method is adopted, the thickness of the metal mold is preferably 50-100 μm, for example, it can be 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or any value between 50-100 μm.
[0055] According to an embodiment of the present application, the thickness of the metal mold 100 is 20-100 μm. When the thickness of the metal mold 100 is within the above range, it can ensure that the pattern can be evenly distributed to achieve the desired visual effect. Too much or too little thickness of the metal mold 100 will cause uneven or unclear patterns on the sample surface.
[0056] For example, the thickness of the metal mold 100 may be 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, or any value between 20 and 100 μm.
[0057] According to an embodiment of the present application, the pulse width of the laser shock wave is greater than or equal to 10ns and less than 30ns. When the pulse width of the laser shock wave is within the above range, it is ensured that the sample patterning area can be quickly covered while maintaining the clarity and accuracy of the pattern. If the pulse width is too small, the short pulse width may cause a decrease in processing accuracy due to uneven energy distribution, especially in areas that require fine processing. If the pulse width is too large, the interaction time between the laser and the material will be too long, increasing the range of the heat-affected zone, thereby reducing the processing accuracy and the clarity of the pattern.
[0058] Since long pulse width can provide higher total energy, long pulse width is often suitable for large-area processing; while short pulse width is suitable for small areas that require detailed processing. When selecting pulse width, it is necessary to comprehensively consider the requirements of processing efficiency and processing accuracy to ensure the best processing effect.
[0059] For example, the pulse width of the laser shock wave can be 10ns, 11ns, 12ns, 13ns, 14ns, 15ns, 16ns, 17ns, 18ns, 19ns, 20ns, 21ns, 22ns, 23ns, 24ns, 25ns, 26ns, 27ns, 28ns, 29ns or any value greater than or equal to 10ns and less than 30ns.
[0060] According to the embodiment of the present application, the energy density of the laser shock wave is 0.5-3.2 GW / cm 2 When the energy density of the laser shock wave is within the above range, it can be ensured that the peak pressure of the shock wave exceeds the dynamic yield strength of the target material, thereby achieving plastic deformation at a high strain rate and obtaining a clear and durable pattern array. The energy of the laser beam determines the pressure of the plasma. If the energy density of the laser shock wave is too large, the metal mold 100 may be damaged and the patterning effect on the sample surface cannot be achieved.
[0061] For example, the energy density of the laser shock wave can be 0.5 GW / cm 2 , 1GW / cm 2 , 1.5GW / cm 2 , 2GW / cm 2 , 2.5GW / cm 2 、3GW / cm 2 、3.2GW / cm 2 Or 0.5-3.2GW / cm 2 Any value in between.
[0062] According to some embodiments of the present application, the laser shock wave is generated by a pulsed laser. The wavelength of the pulsed laser is 355 to 1064 nm. For example, the wavelength of the pulsed laser includes 355 nm, 532 nm and 1064 nm. Using a longer wavelength can induce greater compressive residual stress on the sample surface. In order to optimize the effect of surface patterning, a Nd:YAG pulsed laser with a wavelength of 1064 nm can be selected as the energy source.
[0063] According to an embodiment of the present application, the constraining layer 300 is a tempered glass or a water layer, and the thickness of the constraining layer 300 is 2-8 mm. The transparent constraining layer 300 can limit the hydrodynamic expansion of the laser-induced plasma a, thereby generating a laser-induced shock wave with a high peak pressure.
[0064] For example, the thickness of the constraining layer 300 may be 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, or any value between 2-8 mm.
[0065] Using the method of the present application to treat the metal sample 200 can effectively improve the contact angle and COF of the metal sample 200 to be treated, and can also improve the hardness of the metal sample 200 to be treated, and can improve the wear resistance and durability of the metal sample 200 to be treated.
[0066] The method of the present application can be used to prepare a patterned metal sample. The patterned metal sample has a higher contact angle, a higher COF and a higher hardness, and can be used in multiple fields such as navigation and aircraft. For example, the patterned metal sample has strong hydrophobicity, which can effectively reduce the corrosion rate of the metal in the marine environment, thereby extending the service life of the equipment; in addition, the patterned metal sample can also enhance the anti-icing performance of the material surface, reduce the aircraft navigation resistance and improve navigation safety.
[0067] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0068] Example 1
[0069] Embodiment 1 provides a surface treatment method based on laser shock, comprising:
[0070] (1) Sample surface treatment: Pure titanium was selected as the sample for surface patterning. The sample was polished with 320, 600, 800, 1000 and 1500 mesh wet sandpaper. Fine polishing was performed using 3 μm and 1 μm diamond polishing suspensions, and finally polishing was performed using 0.05 μm colloidal silica suspension to obtain a random surface texture with an average surface roughness of less than 20 nm.
[0071] (2) Mold selection: A brass mesh is used as the metal mold. The overall diameter of the brass mesh is 3 mm and the thickness is 30 μm. Circular holes with a diameter of 90 μm are evenly arranged inside the brass mesh.
[0072] (3) Indirect LSSP process settings: In the indirect LSSP process, a brass mold with evenly arranged circular holes inside is placed on the polished pure titanium surface. The sacrificial layer is made of black tape with a thickness of 80 μm. The sacrificial layer is glued to the side of the brass mold away from the pure titanium sample, so that the brass mold is located between the sacrificial layer and the pure titanium sample. A 2 mm thick flowing water is used as a constraining layer above the sacrificial layer.
[0073] (4) Adjust the following laser parameters: use Nd:YAG pulse laser with a pulse width of 10 ns and a wavelength of 1064 nm as the energy source, and the laser energy density is 0.778 GW / cm 2 Under the action of laser shock wave, a pattern of micro-dent array is formed on the pure titanium sample. The SEM image of the pure titanium surface treated by the method of Example 1 is as follows: Figure 3 As shown by Figure 3 It can be seen that by using the indirect LSSP method to process the smooth pure titanium sample, a circular pit array can be formed on the surface of the pure titanium sample, and the depth of the circular pit pattern is 6.3μm. Figure 4 The change of contact angle of the pure titanium sample before and after treatment by the method of Example 1 shows that the contact angle of the surface before treatment by the method of Example 1 is about 81°. After treatment by the method of Example 1, the contact angle increases to 94.8° after the micro-pattern array is generated on the surface of the pure titanium sample. 2 At the energy density of 1.54W, COF increased from 0.25 to 0.38, an increase of 52%. The surface hardness increased from 112HV to 146HV.
[0074] Example 2
[0075] Embodiment 2 provides a surface treatment method based on laser shock, comprising:
[0076] (1) Sample surface treatment: Pure titanium was selected as the sample for surface patterning. The sample was polished with 320, 600, 800, 1000 and 1500 mesh wet sandpaper. Fine polishing was performed using 3 μm and 1 μm diamond polishing suspensions, and finally polishing was performed using 0.05 μm colloidal silica suspension to obtain a random surface texture with an average surface roughness of less than 20 nm.
[0077] (2) Mold selection: A brass mesh is used as the metal mold. The overall diameter of the brass mesh is 3 mm and the thickness is 30 μm. Circular holes with a diameter of 90 μm are evenly arranged inside the brass mesh.
[0078] (3) Indirect LSSP process settings: In the indirect LSSP process, a brass mold with evenly arranged circular holes inside is placed on the polished pure titanium surface. The sacrificial layer is made of black tape with a thickness of 80 μm. The sacrificial layer is glued to the side of the brass mold away from the pure titanium sample, so that the brass mold is located between the sacrificial layer and the pure titanium sample. A 2 mm thick flowing water is used as a constraining layer above the sacrificial layer.
[0079] (4) Adjust the following laser parameters: use Nd:YAG pulse laser with a pulse width of 10 ns and a wavelength of 1064 nm as the energy source, and the laser energy density is 0.552 GW / cm 2 . A pattern of micro-dimple arrays is formed on a pure titanium sample under the action of laser shock waves.
[0080] The SEM image of the pure titanium surface treated by the method of Example 2 is as follows: Figure 5 As shown by Figure 5 It can be seen that by using the indirect LSSP method to treat the smooth pure titanium sample, a circular micropattern array can be formed on the surface of the pure titanium sample, and the depth of the circular pattern is 5.7μm. Figure 6 The change of contact angle of pure titanium sample before and after treatment by the method of Example 2 is shown. It can be seen that the contact angle of the surface before treatment by the method of Example 2 is about 81°. After treatment by the method of Example 2, the contact angle increases to 83.9° after the micro-pattern array is generated on the surface of the pure titanium sample. Compared with Example 1, Example 2 uses a lower laser energy density, and its surface hydrophobicity is weakened. At 0.552GW / cm 2 At an energy density of 1.547 W, COF increased from 0.25 to 0.31, an increase of 24%. The surface hardness increased from 112 HV to 133 HV.
[0081] Example 3
[0082] Embodiment 3 provides a surface treatment method based on laser shock, comprising:
[0083] (1) Sample surface treatment: Pure iron was selected as the sample for surface patterning. The sample was polished with 320, 600, 800, 1000 and 1500 mesh wet sandpaper. Fine polishing was performed using 9 μm, 3 μm and 1 μm diamond polishing suspensions, and finally polishing was performed using 0.05 μm colloidal silica suspension. A random surface texture with an average surface roughness of less than 20 nm was obtained.
[0084] (2) Mold selection: Brass mesh is used as the metal mold. The overall diameter of the brass mesh is 3 mm and the thickness is 30 μm. The inside of the brass mesh is evenly arranged with a square hole array with a side length of 30 μm.
[0085] (3) Indirect LSSP process settings: In the indirect LSSP process, a brass mold with an array of square holes inside is placed on a polished pure iron surface. The sacrificial layer is made of a black tape with a thickness of 80 μm. The sacrificial layer is adhered to the side of the brass mold away from the pure iron sample, so that the brass mold is located between the sacrificial layer and the pure iron sample. A 2 mm thick running water is used as a constraint layer above the sacrificial layer.
[0086] (4) Adjust the following laser parameters: use Nd:YAG pulse laser with a pulse width of 10 ns and a wavelength of 1064 nm as the energy source, and the laser energy density is 0.552 GW / cm 2 An array of micro-dimples is patterned on a pure iron sample under the action of laser shock waves.
[0087] The SEM image of the pure iron surface treated by the method of Example 3 is as follows: Figure 7 As shown by Figure 7 It can be seen that the indirect LSSP method can form a square pit array on the surface of the smooth pure iron sample, and the surface hardness also increases from 203HV to 221HV.
[0088] Example 4
[0089] Embodiment 4 provides a surface treatment method based on laser shock, comprising:
[0090] (1) Sample surface treatment: AZ31B magnesium alloy was selected as the sample for surface patterning. The sample was polished with 320, 600, 800, 1000 and 1500 mesh wet sandpaper. Fine polishing was performed using 9 μm, 3 μm and 1 μm diamond polishing suspensions, and finally polishing was performed using 0.05 μm colloidal silica suspension to obtain a random surface texture with an average surface roughness of less than 20 nm.
[0091] (2) Mold selection: A brass mesh is used as the metal mold. The overall diameter of the brass mesh is 3 mm and the thickness is 30 μm. The inside of the brass mesh is evenly arranged with a square hole array with a side length of 20 μm.
[0092] (3) Indirect LSSP process settings: In the indirect LSSP process, a brass mold with an array of square holes inside is placed on the polished AZ31B magnesium alloy surface. The sacrificial layer is made of black tape with a thickness of 80 μm. The sacrificial layer is adhered to the side of the brass mold away from the AZ31B magnesium alloy sample, so that the brass mold is located between the sacrificial layer and the AZ31B magnesium alloy sample. A 2 mm thick flowing water is used as a constraining layer above the sacrificial layer.
[0093] (4) Adjust the following laser parameters: use Nd:YAG pulse laser with a pulse width of 10 ns and a wavelength of 1064 nm as the energy source, and the laser energy density is 0.552 GW / cm 2 . Patterns of micro-dimple arrays were formed on AZ31B magnesium alloy samples under the action of laser shock waves.
[0094] The SEM image of the surface of AZ31B magnesium alloy treated by the method of Example 4 is as follows: Figure 8 As shown by Figure 8 It can be seen that the indirect LSSP method can be used to treat the smooth AZ31B magnesium alloy sample to form a square micro-pattern array on the surface of the AZ31B magnesium alloy sample. The hardness of the AZ31B magnesium alloy sample not treated by the method of Example 4 is 73VHN (Vickers hardness value), and the hardness of the AZ31B magnesium alloy sample treated by the method of Example 4 increases to 88VHN. The increase in hardness is attributed to the work hardening effect caused by the laser shock load, and is expected to improve the wear resistance of the magnesium alloy.
[0095] Example 5
[0096] Embodiment 5 provides a surface treatment method based on laser shock, comprising:
[0097] (1) Sample surface treatment: 1045 steel was selected as the sample for surface patterning. The sample was polished with 320, 600, 800, 1000 and 1500 mesh wet sandpaper. Fine polishing was performed using 9 μm, 3 μm and 1 μm diamond polishing suspensions, and finally polishing was performed using 0.05 μm colloidal silica suspension. A random surface texture with an average surface roughness of less than 20 nm was obtained.
[0098] (2) Mold selection: A brass mesh is used as the metal mold. The overall diameter of the brass mesh is 3 mm and the thickness is 80 μm. The inside of the brass mesh is evenly arranged with a rectangular hole array with a length of 30 μm and a width of 10 μm.
[0099] (3) Direct LSSP process settings: In the direct LSSP process, a black tape with a thickness of 80 μm is selected as the sacrificial layer, and the sacrificial layer is placed on the polished 1045 steel surface. A brass mold with a rectangular hole array inside is placed on the side of the sacrificial layer away from the 1045 steel, so that the sacrificial layer is located between the brass mold and the 1045 steel. A 2 mm thick flowing water is used as a constraining layer above the sacrificial layer.
[0100] (4) Adjust the following laser parameters: use Nd:YAG pulse laser with a pulse width of 10 ns and a wavelength of 1064 nm as the energy source, and the laser energy density is 0.552 GW / cm 2A pattern of micro-bump arrays is formed on a 1045 steel sample under the action of laser shock waves.
[0101] The SEM image of the surface of 1045 steel treated by the method of Example 5 is as follows: Fig. 9 As shown by Fig. 9 It can be seen that the smooth 1045 steel sample can be treated with direct LSSP to form a rectangular protruding micropattern array on the surface of the 1045 steel sample. After the 1045 steel sample is treated with direct LSSP, the contact angle of the 1045 steel is increased from 81° to 98° due to the generation of the protruding micropattern array, and the hydrophobic property of the surface is enhanced.
[0102] Comparative Example 1
[0103] (1) Sample surface treatment: Pure titanium was selected as the sample for surface patterning. The sample was polished with 320, 600, 800, 1000 and 1500 mesh wet sandpaper. Fine polishing was performed using 3 μm and 1 μm diamond polishing suspensions, and finally polishing was performed using 0.05 μm colloidal silica suspension to obtain a random surface texture with an average surface roughness of less than 20 nm.
[0104] (2) Mold selection: A brass mesh is used as the metal mold. The overall diameter of the brass mesh is 3 mm and the thickness is 30 μm. Circular holes with a diameter of 90 μm are evenly arranged inside the brass mesh.
[0105] (3) Indirect LSSP process settings: In the indirect LSSP process, a brass mold with evenly arranged circular holes inside is placed on the polished pure titanium surface. The sacrificial layer is made of black tape with a thickness of 80 μm. The sacrificial layer is glued to the side of the brass mold away from the pure titanium sample, so that the brass mold is located between the sacrificial layer and the pure titanium sample. A 2 mm thick flowing water is used as a constraining layer above the sacrificial layer.
[0106] (4) Adjust the following laser parameters: use Nd:YAG pulse laser with a pulse width of 10 ns and a wavelength of 1064 nm as the energy source, and the laser energy density is 3.25 GW / cm 2 . A pattern of micro-dimple arrays is formed on a pure titanium sample under the action of laser shock waves.
[0107] The SEM image of the pure titanium surface treated by the method of Comparative Example 1 is as follows: Fig.10 As shown by Fig.10 It can be seen that the edges of the circular micro-pattern array are damaged and the depth of the circular pattern is uneven. The surface hardness of the pure titanium sample in Comparative Example 1 also drops from 112 HV to 103 HV. The poor effect of Comparative Example 1 may be caused by the excessive laser energy density in Comparative Example 1.
[0108] Comparative Example 2
[0109] (1) Sample surface treatment: Pure titanium was selected as the sample for surface patterning. The sample was polished with 320, 600, 800, 1000 and 1500 mesh wet sandpaper. Fine polishing was performed using 3 μm and 1 μm diamond polishing suspensions, and finally polishing was performed using 0.05 μm colloidal silica suspension to obtain a random surface texture with an average surface roughness of less than 20 nm.
[0110] (2) Mold selection: A brass mesh is used as the metal mold. The overall diameter of the brass mesh is 3 mm and the thickness is 10 μm. Circular holes with a diameter of 90 μm are evenly arranged inside the brass mesh.
[0111] (3) Indirect LSSP process settings: In the indirect LSSP process, a brass mold with evenly arranged circular holes inside is placed on the polished pure titanium surface. The sacrificial layer is made of black tape with a thickness of 80 μm. The sacrificial layer is glued to the side of the brass mold away from the pure titanium sample, so that the brass mold is located between the sacrificial layer and the pure titanium sample. A 2 mm thick flowing water is used as a constraining layer above the sacrificial layer.
[0112] (4) Adjust the following laser parameters: use Nd:YAG pulse laser with a pulse width of 10 ns and a wavelength of 1064 nm as the energy source, and the laser energy density is 0.778 GW / cm 2 , pure titanium samples were treated using laser shock waves.
[0113] Since the thickness of the mold was too small, Comparative Example 2 did not leave a microarray pattern on the surface of the pure titanium sample.
[0114] Comparative Example 3
[0115] (1) Sample surface treatment: Pure titanium was selected as the sample for surface patterning. The sample was polished with 320, 600, 800, 1000 and 1500 mesh wet sandpaper. Fine polishing was performed using 3 μm and 1 μm diamond polishing suspensions, and finally polishing was performed using 0.05 μm colloidal silica suspension to obtain a random surface texture with an average surface roughness of less than 20 nm.
[0116] (2) Mold selection: A brass mesh is used as the metal mold. The overall diameter of the brass mesh is 3 mm and the thickness is 30 μm. Circular holes with a diameter of 90 μm are evenly arranged inside the brass mesh.
[0117] (3) Indirect LSSP process settings: In the indirect LSSP process, a brass mold with evenly arranged circular holes inside is placed on the polished pure titanium surface. The sacrificial layer is made of black tape with a thickness of 80 μm. The sacrificial layer is glued to the side of the brass mold away from the pure titanium sample, so that the brass mold is located between the sacrificial layer and the pure titanium sample. A 2 mm thick flowing water is used as a constraining layer above the sacrificial layer.
[0118] (4) The energy source is a Nd:YAG pulse laser with a pulse width of 30 ns and a wavelength of 1064 nm. The laser energy density is 0.556 GW / cm 2 , pure titanium samples were treated using laser shock waves.
[0119] Since the pulse width in Comparative Example 3 was too large, no microarray pattern was left on the surface of the pure titanium sample.
[0120] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0121] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A surface treatment method based on laser shock, characterized in that: The method comprises: placing a metal mold with a hollow area between a metal sample to be processed and a constrained layer, irradiating a laser beam onto the metal sample to be processed in a direction perpendicular to the constrained layer, and forming a pattern on the metal sample to be processed under the action of a laser shock wave; The energy density of the laser shock wave is less than 3.25 GW / cm 2 , the thickness of the metal mold is greater than 10 μm, and the pulse width of the laser shock wave is less than 30 ns.
2. The surface treatment method based on laser shock according to claim 1, characterized in that: The material of the metal sample to be processed includes any one of pure titanium, pure iron, magnesium alloy and steel.
3. The surface treatment method based on laser shock according to claim 1, characterized in that: The material of the metal mold includes brass or nickel-based alloy.
4. The surface treatment method based on laser shock according to claim 1, characterized in that: A sacrificial layer is also arranged between the metal sample to be processed and the constraining layer. The sacrificial layer comprises a black organic tape and has a thickness of 50-200 μm.
5. The surface treatment method based on laser shock according to claim 4, characterized in that: The sacrificial layer is located between the constrained layer and the metal mold.
6. The surface treatment method based on laser shock according to claim 4, characterized in that: The sacrificial layer is located between the metal mold and the metal sample to be processed.
7. The surface treatment method based on laser shock according to claim 1, characterized in that: The thickness of the metal mold is 20-100 μm.
8. The surface treatment method based on laser shock according to claim 1, characterized in that: The pulse width of the laser shock wave is greater than or equal to 10 ns and less than 30 ns.
9. The surface treatment method based on laser shock according to claim 1, characterized in that: The energy density of the laser shock wave is 0.5-3.2 GW / cm 2 .
10. The surface treatment method based on laser shock according to any one of claims 1 to 9, characterized in that: The constraint layer is tempered glass or a water flow layer, and the thickness of the constraint layer is 2-8 mm.
Citation Information
Cited By
Laser shock treatment method of silicon steel for high-speed motor rotor
CN121046628A
A laser shock treatment method for silicon steel used in high-speed motor rotors
CN121046628B